N-Power Programme and Poverty Reduction: A Post Beneficiaries Exploration in Niger State, Nigeria - Umar, Kobo Halilu; Dennis, Aidelokhai I.; Timothy, Nmadu; Idris, Abu (NIU Journal of Social Sciences; Vol 11 No 4 (2025): NIU Journal of Social Sciences, Vol. 11 No. 4, December 2025, 2025)
This study investigates the impact of the N-Power programme on poverty reduction in Niger State, with a specific focus on the 2020 Batch A, B, and C beneficiaries. The objectives were to assess the employment status of post-beneficiaries, examine changes in income and living standards, and explore the challenges encountered after exiting the programme. The study adopted a descriptive survey design and employed a quantitative research approach. A sample of 354 respondents was selected from a population of 3,091 beneficiaries using stratified random sampling. Data were collected through structured questionnaires and analyzed using descriptive statistics, paired t-tests, and multiple regression analysis with the aid of Stata 17. The findings revealed that 61.9% of beneficiaries were employed after the programme, with a statistically significant improvement in their income levels and living standards. However, key challenges such as lack of startup capital, difficulty securing permanent employment, and absence of post-exit support were identified. Regression results indicated that employment status, income, skill utilization, and ability to save were significant predictors of poverty reduction. The study concludes that while the N-Power programme has positively influenced the economic conditions of many young Nigerians in Niger State, its long-term impact can be strengthened through post-programme support, access to finance, and improved policy implementation. Recommendations include the provision of soft loans or grants, establishment of mentorship structures, private sector engagement, and development of a beneficiary tracking system to ensure sustainability and continued poverty alleviation.